Possibilities and impossibilities of magnetic nanoparticle use in the control of infectious biofilms. (10th April 2021) - Quan, Kecheng; Zhang, Zexin; Ren, Yijin; Busscher, Henk J.; van der Mei, Henny C.; Peterson, Brandon W.
Highlights: Papers on magnetic targeting of NPs should always present magnetic field conditions. Biofilm targeting of magnetic NPs is impossible with currently available techniques. Magnetically-propelled NPs can disrupt biofilms without precise targeting. Biofilm channels made using magnetically-propelled NPs enhance antibiotic penetration. Abstract: Targeting of chemotherapeutics towards a tumor site by magnetic nanocarriers is considered promising in tumor-control. Magnetic nanoparticles are also considered for use in infection-control as a new means to prevent antimicrobial resistance from becoming the number one cause of death by the year 2050. To this end, magnetic nanoparticles can either be loaded with an antimicrobial for use as a delivery vehicle or modified to acquire intrinsic antimicrobial properties. Magnetic nanoparticles can also be used for the local generation of heat to kill infectious microorganisms. Although appealing for tumor- and infection-control, injection in the blood circulation may yield reticuloendothelial uptake and physical obstruction in organs that yield reduced targeting efficiency. This can be prevented with suitable surface modification. However, precise techniques to direct magnetic nanoparticles towards a target site are lacking. The problem of precise targeting is aggravated in infection-control due to the micrometer-size of infectious biofilms, as opposed to targeting of nanoparticles towards centimeter-sized tumors. This review aims to identify possibilities and impossibilities of magnetic targeting of nanoparticles for infection-control. We first review targeting techniques and the spatial resolution they can achieve as well as surface-chemical modifications of magnetic nanoparticles to enhance their targeting efficiency and antimicrobial efficacy. It is concluded that targeting problems encountered in tumor-control using magnetic nanoparticles, are neglected in most studies on their potential application in infection-control. Currently biofilm targeting by smart, self-adaptive and pH-responsive, antimicrobial nanocarriers for instance, seems easier to achieve than magnetic targeting. This leads to the conclusion that magnetic targeting of nanoparticles for the control of micrometer-sized infectious biofilms may be less promising than initially expected. However, using propulsion rather than precise targeting of magnetic nanoparticles in a magnetic field to traverse through infectious-biofilms can create artificial channels for enhanced antibiotic transport. This is identified as a more feasible, innovative application of magnetic nanoparticles in infection-control than precise targeting and distribution of magnetic nanoparticles over the depth of a biofilm.